2008
DOI: 10.1002/ev.269
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofits and evaluation: Managing expectations from the leader's perspective

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
19

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 10 publications
0
27
0
19
Order By: Relevance
“…However, demonstrating ac countability for funders has become essential for NGO survival in competitive environments (Carman & Fredericks, 2010;Cousins, Goh, Elliott, & Bourgeois, 2014;McCoy, Rose, & Connolly, 2013). Increasingly, NGOs are embracing evaluation's potential as a vehicle for accountability and program improve ment (Alaimo, 2008;Moxham, 2014). This need for information necessitates increased focus on organizational evaluation literacy for NGOs' ongoing sus tainability.…”
Section: Mots Clés : éValuation Littératie En Matière D' éValuationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, demonstrating ac countability for funders has become essential for NGO survival in competitive environments (Carman & Fredericks, 2010;Cousins, Goh, Elliott, & Bourgeois, 2014;McCoy, Rose, & Connolly, 2013). Increasingly, NGOs are embracing evaluation's potential as a vehicle for accountability and program improve ment (Alaimo, 2008;Moxham, 2014). This need for information necessitates increased focus on organizational evaluation literacy for NGOs' ongoing sus tainability.…”
Section: Mots Clés : éValuation Littératie En Matière D' éValuationmentioning
confidence: 99%
“…Theories of evaluation use can assist in understanding the different ways in which NGO employees engage with evaluation. Evaluation use is typically split into fi nd ings use and process use (Alkin & Taut, 2003). The literature identifies three main types of findings use: instrumental, conceptual, and symbolic (Kirkhart, 2000).…”
Section: Evaluation Use and Internal Evaluationmentioning
confidence: 99%
“…evaluation findings) to make changes; (b) is integrated with work activities, and within the organization's infrastructure (e.g., its culture, systems and structures, and leadership and communication mechanisms); and (c) invokes the alignment of values, attitudes, and perception's among organizational members." Alaimo (2008) noted that "evaluation becomes a part of organizational learning when it is institutionalized as part of the organization's information, power structure, processes, and systems that influence decision making and action" (p. 77).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Organizations that engage in evaluation as an honest, transparent, and ongoing discussion rather than as a bureaucratic process become learning cultures driven by leadership who is willing to learn from mistakes, reward good ideas, and encourage staff toward continuous improvement (Hoole & Patterson, 2008). Alaimo (2008) found that CEOs who encouraged evaluation activity as programdriven and outcome-focused (versus donor agency accountability driven) 1) hired staff dedicated to evaluation, 2) used evaluation results to improve programs, and 3) demonstrated a long-term commitment for program evaluation.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…In general, partner agency staff increased understanding of how to measure outcomes but inconsistent growth in the ability to implement the measures on their own. Leaders who prioritize evaluation are more likely to create a sustainable evaluation system than those who evaluate programs as a matter of compliance for funders (Alaimo, 2008). While the art organization partners worked hard on evaluation during the YEA Initiative, only one -which had less turnover -appeared able to maintain the capacity once the initiative ended.…”
Section: Innovation For Community Impactmentioning
confidence: 99%